PEMODELAN SPASIAL BAHAYA TSUNAMI DAN KETERPAPARANYA TERHADAP PERMUKIMAN DI KOTA AMBON - Heinrich Rakuasa; Melianus Salakory (Jurnal Sains Informasi Geografi (J SIG), 2022)
Ambon City is an area that has the highest disaster risk index in Maluku Province. The direction of development of residential areas in Ambon City tends to be coastal areas which will certainly have an impact on the risk of tsunami hazards. This study aims to spatially model the tsunami hazard and its exposure to settlements in Ambon City. The tsunami hazard was analyzed using the variables of land height, slope, distance from the river, and distance from the shoreline, while the level of exposure was analyzed based on the results of the tsunami hazard overlay and settlement variables. This study uses an overlay technique on variables that have been scored and analyzed using a Geographic Information System (GIS) approach. The results show that the tsunami hazard in Ambon City is dominated by a low tsunami hazard level which has a wider area compared to the medium and high tsunami hazard classes, this is because 77.32% of the Ambon City area is at an altitude of > 64 masl while the tsunami exposure level in settlements in Ambon City is nominated by a high hazard level with an area of 2,835,33 ha, this is because almost a large part of the population in Ambon City lives in coastal areas, this can increase the risk of a tsunami disaster. The Ambon City Government plays an important role in disaster risk reduction efforts by continuously improving its adaptive capacity indicators and preparing for future disaster mitigation-based spatial planning.